Prosedur Audit dalam Menilai Kewajaran Penyajian Akun Pendapatan oleh KAP HXX di Koperasi JAS Tahun 2024 - Riska Amelia; Maria Patricia Dea Wulandari; Muhammad Hasbi; Ridwan Zulpi Agha (-, 2026)
This study aims to explain the audit procedures carried out by the Public Accounting Firm (KAP) HXX in assessing the fairness of revenue presentation in the 2024 financial statements of Cooperative JAS. Cooperative JAS is a cooperative engaged in employee daily needs services and savings and loan activities. During the audit process, it was found that the cooperative classified loan interest income from members amounting to IDR130,193,203 as other income, whereas according to the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP), such income should be recorded as operating revenue. This research employs a qualitative method with a case study approach. Primary data were obtained through interviews with auditors from KAP HXX, while secondary data came from working papers and management letters. The results indicate that the audit procedures included understanding the entity and its environment, performing substantive testing, and analyzing management assertions related to revenue accounts. The auditor recommended reclassifying loan interest income to operating revenue in compliance with applicable accounting standards. Implementing this recommendation improved the transparency and fairness of  Koperasi JAS’s financial statements presentation. These findings highlight the importance of proper audit procedures in detecting revenue misclassification and ensuring the reliability of cooperative financial reporting.